Mary Wollstonecraft, Social Constructivism, and the Idea of Freedom. Issue 4 (December 2019) - Hirschmann, Nancy J.; Regier, Emily F.
Abstract: This article considers Mary Wollstonecraft as a theorist of freedom for women through the lens of social constructivism. Previous republican readings of Wollstonecraft as promoting a vision of freedom as independence or non-domination are compromised by their underpinnings in liberal individualism. Instead, we suggest her theory displays elements of positive liberty and particularly what we call "subjectivity freedom." Reading Wollstonecraft as an early social constructivist, we show her grappling with how women's subjectivity is constructed in patriarchal societies such that they desire the conditions of their own subordination. This troubles the very notion of domination and its putative opposite, freedom-as-independence. Paradoxically, while noting how women's sense of self was profoundly and intimately shaped by the patriarchal structures they inhabited, Wollstonecraft's own argument was limited by these same constructions. Nonetheless, she struggled to conceive a radically emancipatory vision of women's lives, aspirations, and desires from within the confines of a context and discourse premised on their devaluation. A social constructivist approach shows that Wollstonecraft sought not simply to change women or specific structures of male dominance, but rather the processes within which men and women defined gender, the family, and personal identity: in short, their subjectivity.